2005
DOI: 10.1007/s10554-004-6923-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress echocardiography: the long and winding road from meta-analysis to bedside

Eugenio Picano

Abstract: In response to the article by Noguchi et al. (Int. J. Cardiovascular Imaging 21,[189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207] In this issue, Noguchi et al. perform yet another meta-analysis in order to address the issue of which test is better for stress echocardiography [1]. The subject is an important one, and the authors meritoriously go through an extensive, 20-years long journey across the stress echo literature to reach some evidence-based conclusions: ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the other hand, an exhaustive meta‐analysis from 2005 concluded that adenosine SE is less sensitive than dobutamine and exercise SE . This statement has been questioned by proponents of vasodilator stress . 2D strain analysis has proved to be more sensitive than wall motion analysis, but a limitation to the technique is the relative low temporal resolution (50–90 frames per second) which—at least in theory—is a disadvantage when the heart rate is high, as it is during dobutamine infusion or exercise stress, but not during vasodilatation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an exhaustive meta‐analysis from 2005 concluded that adenosine SE is less sensitive than dobutamine and exercise SE . This statement has been questioned by proponents of vasodilator stress . 2D strain analysis has proved to be more sensitive than wall motion analysis, but a limitation to the technique is the relative low temporal resolution (50–90 frames per second) which—at least in theory—is a disadvantage when the heart rate is high, as it is during dobutamine infusion or exercise stress, but not during vasodilatation …”
Section: Discussionmentioning
confidence: 99%
“…17 This statement has been questioned by proponents of vasodilator stress. 18 2D strain analysis has proved to be more sensitive than wall motion analysis, but a limitation to the technique is the relative low temporal resolution (50-90 frames per second)…”
Section: Discussionmentioning
confidence: 99%
“…40 Dipyridamole had superior specificity for CAD than ESE, DSE or dipyridamole SPECT, although the sensitivity is lower, especially for one-vessel disease. 33,40,41 The specificity of DSE can be enhanced by using high-dose protocols or by fiGUre 4 Calculation of wall motion segment index with DSE. All segments are observed at baseline, during low-dose dobutamine infusion, at peak heart rate and at recovery.…”
Section: Diagnostic Accuracy Of Stress Echocardiographymentioning
confidence: 99%